2008
DOI: 10.1111/j.1365-246x.2007.03653.x
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational torque on the inner core and decadal polar motion

Abstract: S U M M A R YA decadal polar motion with an amplitude of approximately 25 milliarcsecs (mas) is observed over the last century, a motion known as the Markowitz wobble. The origin of this motion remains unknown. In this paper, we investigate the possibility that a time-dependent axial misalignment between the density structures of the inner core and mantle can explain this signal. The longitudinal displacement of the inner core density structure leads to a change in the global moment of inertia of the Earth. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 53 publications
(104 reference statements)
0
26
0
Order By: Relevance
“…But because equatorial torques do not break the Taylor constraint, their consequence on the core surface flow cannot be easily identified. Nonetheless their magnitude can be roughly estimated and shown to also be compatible with the weak and poorly resolved decade Hulot et al 1996;Dumberry 2008a). …”
Section: Large Scale Core Flowsmentioning
confidence: 80%
See 1 more Smart Citation
“…But because equatorial torques do not break the Taylor constraint, their consequence on the core surface flow cannot be easily identified. Nonetheless their magnitude can be roughly estimated and shown to also be compatible with the weak and poorly resolved decade Hulot et al 1996;Dumberry 2008a). …”
Section: Large Scale Core Flowsmentioning
confidence: 80%
“…These are a special type of Alfvén wave that propagate along the cylindrically radial component of the magnetic field perpendicular to Earth's rotation axis (see e.g. Dumberry 2008b where an accessible introductory account is given). Figure 21 shows schematically the geometrical form of torsional oscillations.…”
Section: Torsional Oscillations and Magnetostrophic Wavesmentioning
confidence: 99%
“…(A.18) since it is also valid for a non-homogenous internal layer, as has been shown by e.g. Dumberry (2008) in the particular case of the gravitational torque on the inner core of the Earth due to the outer core, mantle and crust.…”
mentioning
confidence: 77%
“…From the angular momentum equations for the ocean (12) and for the liquid 21 core (14), we then have, in the Poincaré approximation (ḣ o andḣ f 0),…”
Section: Internal Pressure Torquesmentioning
confidence: 99%
“…But when Mound (2005) examined this mechanism, he concluded that while torsional oscillations may excite both decadal LOD and polar motion variations, when the oscillations are constrained to match the observed LOD amplitude, the resulting electromagnetic torque on the inner core is too weak to excite decadal polar motions to their observed level. Dumberry (2008) further studied the influence of the inner core on polar motion by examining the gravitational coupling between the inner core and density heterogeneities in the mantle. He found that his model is capable of producing decadal polar motions having amplitudes as large as those observed and that are polarized about a longitudinal axis.…”
Section: True Polar Wander and Glacial Isostatic Adjustmentmentioning
confidence: 99%